Social Accountability in a Socio-Cultural Framework: Exploring “Lapau” as an Arena for Budgeting Planning in Salayo Village, Solok Regency, West Sumatera Province - Arya Ananta Pramudya; Hendri Koeswara; Desna Aromatica (Journal of Political and Governance Studies, 2026)
Background This study investigates the role of 'lapau' as a mechanism for social accountability in the budget planning of the Salayo Nagari government. Set within the framework of village autonomy as defined by Law Number 6 of 2014, the research addresses the disparity between formal, procedural accountability and the substantive community practices that exist in reality. Methods Through qualitative methodology involving interviews, observations and document analysis, the study identifies 'Lapau' as a critical informal public sphere. The presence of government officials within the 'Lapau' reduces social distance and encourages continuous dialogue, which contributes to greater public trust and responsiveness. Results The findings suggest that this social arena facilitates transparency, direct discourse and rapid problem solving, thereby overcoming the limitations of rigid formal procedures.  Instead of replacing the formal accountability mechanisms, the 'Lapau' works with the institutional arrangements that already exist by embedding accountability practices within social and cultural relations. Conclusions Ultimately, the 'Lapau' strengthens the Nagari government's legitimacy and fosters a deeper emotional bond with the community, ensuring a sustainable response to citizen aspirations.